Postabortion Contraception Acceptance and Associated Factors in Dessie Health Center and Marie Stopes International Clinics, South Wollo Northeast, Amhara Region, 2017 - Abebe, Ayele Mamo; Wudu Kassaw, Mesfin; Estifanos Shewangashaw, Nathan (International Journal of Reproductive Medicine, 2019)
Introduction. Abortion is termination of pregnancy before the viability of the pregnancy. It is one of the major causes for maternal mortality in the world and in Ethiopia. Unintended pregnancies which end up in abortion occur due to contraception method nonuse or misuse. To limit unintended pregnancies and avoid repeated abortions promoting immediate postabortion contraception is crucial. Objective. To assess the proportion of postabortion contraception acceptance among women who got abortion care service and factors associated with it in Marie stopes international clinic and Dessie health center, Dessie, North eastern Amhara, 2017. Methods. An institutional based cross-sectional study design was conducted from May 1 to May 30, 2017, at Marie stopes international clinics and Dessie health center. A sample of 125 women were selected by means of systematic sampling techniques and 118 abortion clients were interviewed in Marie stopes international clinic and Dessie on the use/acceptance of postabortion family planning (PAFP). Data were collected through pretested structured questionnaire. Data was cleaned and checked. Chi-square test was done to assess the association between dependent and independent variables. Odds ratio was done to assess the strength of association. Frequency tables, pie chart, and graphs were used to present the finding of the study. Results. From a total of 125 participants recruited, 118 participated in the study while 7 were unwilling to participate in the study, yielding the response rate of 94.4%. Among the 118 study participants, 79 (66.9%) were within the age group 25-34. This study found a strong positive association between Postabortion contraception acceptance and age [P = 0.007 [X2 test= 9.989, COR=2.625)]. Study subjects aged 15–24 years were 3 times more likely to accept postabortion family planning as compared with those aged >35 years. Conclusion and Recommendation. This study revealed that the acceptance of postabortion family planning method was 84%. Age of women, marital status, ever use of history family planning, involvement of others in decision making, and family planning counseling were significantly associated with postabortion family planning acceptance. Therefore it is better to give emphasis on health education about family planning.